1995
DOI: 10.1085/jgp.106.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent open-state inactivation of cardiac sodium channels: gating current studies with Anthopleurin-A toxin.

Abstract: Journal of General Physiology. 106:601-616), we studied Na channel gating currents (Ig) in voltage-clamped single canine cardiac Purkinje cells at ~ 12~ Comparison of Ig recorded in response to step depolarizations before and after modification by Ap-A toxin showed that toxin-modified gating currents decayed faster and had decreased initial amplitudes. The predominate change in the charge-voltage (Q-V) relationship was a reduction in gating charge at positive potentials such that Q~ax was reduced by 33%, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
94
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 59 publications
20
94
0
Order By: Relevance
“…Although there are fewer studies on the discrete transitions in the activation processes of Na channels, the S4's from domains I, II, and III are thought to be principally involved in channel activation (2) while inactivation has been associated with the S4 in DIV (8,10,11,21,22,37,43,44). Studies of individual florescent-tagged voltage sensors in rat skeletal muscle Na channels (rSkM1, Na V 1.4) showed that the S4's in domains I-III all translocated rapidly during a step depolarization consistent with their role in the activation process (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are fewer studies on the discrete transitions in the activation processes of Na channels, the S4's from domains I, II, and III are thought to be principally involved in channel activation (2) while inactivation has been associated with the S4 in DIV (8,10,11,21,22,37,43,44). Studies of individual florescent-tagged voltage sensors in rat skeletal muscle Na channels (rSkM1, Na V 1.4) showed that the S4's in domains I-III all translocated rapidly during a step depolarization consistent with their role in the activation process (10).…”
Section: Discussionmentioning
confidence: 99%
“…I Na decay in WT channels is critically dependent upon inactivation from the open state (8,11,14,21,22,37,43,44); consequently the more rapid decay of I Na following stabilization of the DII-S4 suggests that inactivation has also become faster. Furthermore, the large negative shift in the V ½ of the steady-state Na channel availability curve after DII-S4 was stabilized also suggests it has a role in closed state inactivation, presumably by helping form or helping control Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Site-specific fluorescent labeling of the S4 segment of Na V 1.4 demonstrated the effect of stabilizing S4 of DI and DIV through α-scorpion toxin binding [236]. Both sea anemone and α-scorpion toxins have been shown to enhance the recovery of inactivation [232,237]. As the S4 region is responsible for voltagedependant gating, toxins that interact with this region are referred to as gating modifier toxins.…”
Section: Site 3 and Sitementioning
confidence: 99%